Sharp injuries during clinical training among medical students in the University of Peradeniya, Sri Lanka - Dalugama, Chamara; Gamage, Kavishka (International Journal of Occupational Safety and Health, 2023)
Introduction: Medical students are exposed to blood and body fluids during their clinical training which increased the risk of transmission of blood-borne infections. The objective of the study is to assess the prevalence, knowledge, attitudes and practices regarding sharp injuries among final medical students of the University of Peradeniya, Sri LankaMethods: A survey was done among 210 final-year medical students of the University of Peradeniya with a self-administered online questionnaire including demographic information, experience, knowledge and reporting behavior following sharp injuries. Results: Response rate was 80% (n=168). Sharp injuries were experienced by 22.6%. Most of the sharp injuries were sustained during venepuncture (39.5%). The majority (58.9%) did not adhere to universal precautions as they did not anticipate the event. One-third of the students (31.6%) did not know about universal precautions. Most of the students (68.4%) who had a sharp injury did not seek post-exposure assistance or prophylaxis. The majority of this group thought there is no risk (64%). Twenty-five students have not completed the full course of the hepatitis B vaccine. More than half (51.8%) of the fully vaccinated group were unaware of their immune status.  The majority (67.3%) believed that their knowledge is not adequate regarding the prevention and management of needle stick injuries. The majority (97%) believed more emphasis should be given to knowledge and practice regarding sharp injuries.Conclusion: The knowledge, attitudes and practices of medical students regarding the prevention and management of sharp injuries were unsatisfactory. Poor awareness was observed regarding immune status following hepatitis B vaccination among medical students.